Ateo Martí, an anticlerical activist in the Second Spanish Republic (1931-1936) - Ginard Féron, David (Hispania Nova, 2020)
The journalist, small entrepreneur and social activist Mateo Martí Miquel "Ateo Martí" (1889-1936) is one of the most significant figures of anticlericalism in the 1930s Spain. Born in Mallorca, he was a freemason and he was active in republicanism, the PSOE and the PCE, for which he was a candidate in the general election in November 1933. Founder of the Laic League of Mallorca (1930), he run the magazine La Sotana Roja (1931) and promoted the Atheist League (1932-33). During the Second Spanish Republic, he led numerous polemics with the powerful conservative and clerical sectors of the island. His tragic end, after the coup d’état of July 1936, is highly representative of the fate of a large number of Spanish freethinkers of the first third of the 20th century.